Effect of nectar producing on the reproduction of Diadegma aff insulare Cresson (Hymenoptera: Ichneumonidae), parasitoid of Plutella xylostella L. (Lepidoptera: Plutellidae) - CARRILLO, DANIEL; SERRANO, MIGUEL S.; TORRADO-LEÓN, EDISON (Revista Colombiana de Entomología, 2006)
The effect of nectar-producing plants (Brassica rapa (L.), Calendula officinalis (L.), Ruta graveolens (L.), and Borrago officinalis (L.)), compared to honey solution, on the longevity and fecundity of Diadegma aff. insulare were studied under green house conditions. The longevity and fecundity of D. insulare females fed on B. rapa (L.) were similar to those fed with a solution of honey and water (15,4±1,1 days, 67,0± 2,7 progeny/female). B. officinalis was the best food source (38,4±4,6 days, 186,8±2,5 progeny/female), followed by R. graveolens (18,2±10,6 days, 91,4±2,7 progeny). Females fed with C. officinalis (4,0±1,7 days, 12.2±2,97 progeny) had the lowest fecundity and longevity with respect to the control. The longevity and fecundity of D. insulare varied with morphological characters of flowers. An increase in longevity and fecundity was correlated with a greater width and length of the corolla. In choice and no choice tests, a greater number of flower visits were recorded for R. graveolens (4,2±1,7 y 5,75±1,2 visits/min) and B. rapa (3,8±0,9 y 5,75±0,9 visits/min). It is suggested that the number of nectar producing plants, especially B. officinalis, be manipulated to increase the impact of D. insulare on the integrated management of P. xylostella.